2017
DOI: 10.1097/rli.0000000000000347
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Tomography Evaluation of Breast Density

Abstract: ObjectivesUltrasound tomography (UST) is an emerging whole-breast 3-dimensional imaging technique that obtains quantitative tomograms of speed of sound of the entire breast. The imaged parameter is the speed of sound which is used as a surrogate measure of density at each voxel and holds promise as a method to evaluate breast density without ionizing radiation. This study evaluated the technique of UST and compared whole-breast volume averaged speed of sound (VASS) with MR percent water content from noncontras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In this paper, we describe the results of an exploratory case-control study aimed at assessing breast sound speed as a risk factor for breast cancer. The study builds upon our previous work showing that sound speed is a surrogate measure of BD [24][25][26][27][28][29] and, by inference, a potential risk factor for breast cancer. The motivation for our current study was to explore whether UST-derived sound speed is associated with breast cancer risk.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…In this paper, we describe the results of an exploratory case-control study aimed at assessing breast sound speed as a risk factor for breast cancer. The study builds upon our previous work showing that sound speed is a surrogate measure of BD [24][25][26][27][28][29] and, by inference, a potential risk factor for breast cancer. The motivation for our current study was to explore whether UST-derived sound speed is associated with breast cancer risk.…”
Section: Introductionmentioning
confidence: 83%
“…Potential reasons for the stronger observed effects for VASS versus MPD include the true volumetric nature of BD assessment by UST of the uncompressed breast. Indeed, prior work has shown that VASS is strongly correlated with other volumetric breast imaging metrics, such as automated volumetric measures from mammography [28] as well as MRI percent water content [25]. However, in contrast to MRI, UST is a cost-effective (similar price as digital mammography) and rapid imaging strategy, requiring a water source and computer to complete the scan in 2-3 min (versus up to 45 min for MRI), without contrast or a specialized exam room.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dense tissue tends to have high transmission and attenuation of sound (characterized as white on the tomographic image), while fatty tissue demonstrates low-sound speed and low attenuation (appears as dark on the tomographic image). Given these parameters some authors have suggested that it can provide a surrogate measure of breast density [62]. Others suggest that it can improve specificity by determining solid masses from complicated cysts [63].…”
Section: Quantitative Breast Ultrasoundmentioning
confidence: 99%